2022
DOI: 10.3389/fimmu.2022.949746
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dietary polyphenol supplementation in the treatment of non-alcoholic fatty liver disease: A systematic review and meta-analysis

Abstract: BackgroundDietary polyphenol treatment of non-alcoholic fatty liver disease (NAFLD) is a novel direction, and the existing clinical studies have little effective evidence for its therapeutic effect, and some studies have inconsistent results. The effectiveness of dietary polyphenols in the treatment of NAFLD is still controversial. The aim of this study was to evaluate the therapeutic efficacy of oral dietary polyphenols in patients with NAFLD.MethodsThe literature (both Chinese and English) published before 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 156 publications
5
21
1
Order By: Relevance
“…Daily intake of 1,500 mg curcumin could reduce serum cholesterol, glucose, and ALT in patients with NAFLD ( 40 ). A study of systematic review and meta-analysis showed that curcumin, naringenin, hesperidin, catechin, and silymarin may have therapeutic efficacy in patients with NAFLD ( 41 ). The result of our study on anthocyanins is complementary to the research on the correlation between polyphenols and MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Daily intake of 1,500 mg curcumin could reduce serum cholesterol, glucose, and ALT in patients with NAFLD ( 40 ). A study of systematic review and meta-analysis showed that curcumin, naringenin, hesperidin, catechin, and silymarin may have therapeutic efficacy in patients with NAFLD ( 41 ). The result of our study on anthocyanins is complementary to the research on the correlation between polyphenols and MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The control group, NASH patients, perceived regular treatment (silymarin, omega 3, and vitamin E) [25,26]. In the treated group, NASH patients received regular treatment plus PTX (400 mg 3 times daily) after meals for 6 months, following the approval of the Ethical Committee and obtained informed consent from recruited subjects.…”
Section: Methodsmentioning
confidence: 99%
“…According to the results of included studies' quality assessment by the AMSTAR2 questionnaire (Table S3), three cases of included studies were of high quality and eight cases were of moderate quality. However, three studies (Fakhri et al, 2022;Mansour-Ghanaei et al, 2019;Yang et al, 2022) did not assess the presence and likely impact of publication bias because of the low number of included studies. Moreover, using the GRADE system, all quality effects were rated as moderate (Table 3).…”
Section: Methodological Qualitymentioning
confidence: 99%
“…The duration of curcumin supplementation ranged from 4 to 24 weeks. The location of the studies was as follows: six in Iran (Baziar & Parohan, 2020;Fakhri et al, 2022;Goodarzi et al, 2019;Jafarirad et al, 2019;Jalali et al, 2020;Mansour-Ghanaei et al, 2019), three in China (Wei et al, 2019;Yang et al, 2022;Zhou et al, 2021), one in Australia (Khalili & Nammi, 2022), and one case in Malaysia (Ngu et al, 2022). As shown in Table 2, all of the included meta-analyses evaluated the quality of their included randomized controlled trials using Cochrane (10 cases) and Jaded scales (one case) and reported a good quality for their included studies.…”
Section: Study Characteristicsmentioning
confidence: 99%